2021
DOI: 10.1088/1755-1315/648/1/012212
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of numerous machine learning algorithms performance in classifying rice growth stages based on Sentinel-2 to enhance crop monitoring in national level

Abstract: The rice monitoring based on Sentinel-2 (SC-S2) has been developed for over nine months. It has been observed as the first and only system which generate rice growth stages maps in 10 m spatial resolution using machine learning in Indonesia. However, the SC-S2 use Support Vector Machine to separate the rice growth stages, which may have poor performances. The objective of this study is to investigate the performance of other classifiers to increase the performance of SC-S2. We used survey data from the field c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies have shown that, among these satellite products, the spatial resolution of optical images used for classification has little effect on the accuracy of classification in areas with large parcels, while Sentinel-2 images can provide better classification results than Landsat and MODIS images for areas with fragmented farmland [12]. Many scholars have carried out research on crop classification based on Sentinel-2 images [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that, among these satellite products, the spatial resolution of optical images used for classification has little effect on the accuracy of classification in areas with large parcels, while Sentinel-2 images can provide better classification results than Landsat and MODIS images for areas with fragmented farmland [12]. Many scholars have carried out research on crop classification based on Sentinel-2 images [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%